Immune and Genetic Signatures of Breast Carcinomas Triggering Anti-Yo–Associated Paraneoplastic Cerebellar Degeneration. Issue 5 (12th September 2022) - Peter, Elise; Treilleux, Isabelle; Wucher, Valentin; Jougla, Emma; Vogrig, Alberto; Pissaloux, Daniel; Paindavoine, Sandrine; Berthet, Justine; Picard, Géraldine; Rogemond, Véronique; Villard, Marine; Vincent, Clémentine; et al.
Abstract : Background and Objectives: Paraneoplastic cerebellar degeneration (PCD) with anti-Yo antibodies is a cancer-related autoimmune disease directed against neural antigens expressed by tumor cells. A putative trigger of the immune tolerance breakdown is genetic alteration of Yo antigens. We aimed to identify the tumors' genetic and immune specificities involved in Yo-PCD pathogenesis. Methods: Using clinicopathologic data, immunofluorescence (IF) imaging, and whole-transcriptome analysis, 22 breast cancers (BCs) associated with Yo-PCD were characterized in terms of oncologic characteristics, genetic alteration of Yo antigens, differential gene expression profiles, and morphofunctional specificities of their in situ antitumor immunity by comparing them with matched control BCs. Results: Yo-PCD BCs were invasive carcinoma of no special type, which early metastasized to lymph nodes. They overexpressed human epidermal growth factor receptor 2 (HER2) but were hormone receptor negative. All Yo-PCD BCs carried at least 1 genetic alteration (variation or gain in copy number) on CDR2L, encoding the main Yo antigen that was found aberrantly overexpressed in Yo-PCD BCs. Analysis of the differentially expressed genes found 615 upregulated and 54 downregulated genes in Yo-PCD BCs compared with HER2-driven control BCs without PCD. Ontology enrichment analysis found significantly upregulated adaptive immune response pathways in Yo-PCD BCs. IF imaging confirmed an intense immune infiltration with an overwhelming predominance of immunoglobulin G–plasma cells. Discussion: These data confirm the role of genetic alterations of Yo antigens in triggering the immune tolerance breakdown but also outline a specific biomolecular profile in Yo-PCD BCs, suggesting a cancer-specific pathogenesis.